Peranan Penyidikan Tambahan dalam Menindaklanjuti Perkara Tindak Pidana Pencurian Sapi di Wilayah Hukum Polsek Petang - Ni Komang Diana Trisnayanti; Anak Agung Sagung Laksmi Dewi; Ni Made Suryati Karma (Jurnal Preferensi Hukum, 2022)
Handling the crime of theft is certainly an alternative in the criminal justice system. In the investigation effort, of course, there can be obstacles that affect the slowness of the examination of the case, as happened at the Evening Police, namely the lack of complete evidence needed because there is a shortage of investigating officers. Therefore, the role of additional investigators is very much needed for the Evening Police. This study uses empirical research methods as well as a sociological approach to law. The role of additional investigations in the settlement of cases of cow theft in the jurisdiction of the Evening Police Sector is to be able to complete the prosecutor's instructions through P-19 which is a code that the results of the investigation are not complete, however, sometimes investigators cannot fulfill the prosecutor's instructions, so the case files go back and forth up to 4 times. . This is done in accordance with the provisions of the legislation or operational standards that apply to the Indonesian National Police.